1997
DOI: 10.1093/toxsci/39.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Olestra Absorption in Guinea Pigs with Normal and Compromised Gastrointestinal Tracts

Abstract: Female guinea pigs (12/group) were given a single dose of [ I4 C]-olestra by gavage after consuming either 3% poligeenan in tap water (Compromised group) or just tap water (Normal group) for 5 weeks. A Sentinel group (N = 2) was given 3% poligeenan for 5 weeks. Ten sentinel animals were killed 1 day before and 10 1 day after the other animals were dosed with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A study in an animal model of inflammatory bowel disease showed that mucosal damage did not result in absorption of olestra (52). Guinea pigs with gastrointestinal tract lesions from consumption of poligeenan did not absorb 14 C-labeled olestra as shown by analyses of tissue lipids and sucrose in urine.…”
Section: Olestra Ingestion and Gastrointestinal Transitmentioning
confidence: 99%
“…A study in an animal model of inflammatory bowel disease showed that mucosal damage did not result in absorption of olestra (52). Guinea pigs with gastrointestinal tract lesions from consumption of poligeenan did not absorb 14 C-labeled olestra as shown by analyses of tissue lipids and sucrose in urine.…”
Section: Olestra Ingestion and Gastrointestinal Transitmentioning
confidence: 99%
“…The fatty acids used to make olestra can be derived from any vegetable oil. The molecular structure of olestra 1 is such that it is not broken down by digestive enzymes, 2 and is not absorbed across an intact 3 –5 or structurally compromised gastrointestinal tract 6 . As a result, olestra passes unchanged into the colon and is excreted 7 .…”
Section: Introductionmentioning
confidence: 99%